Coast Guard Plays a Role in Maritime Law Enforcement - Widijowati, Rr.Dijan; Jayawibawa, Marcellus; Budisetyowati, Dwi Andayani (Siber International Journal of Advanced Law (SIJAL), 2025)
Indonesia, as the world's largest archipelagic state, faces complex challenges in maritime law enforcement. The establishment of the Maritime Security Agency (BAKAMLA) as the embryo of the Indonesian Coast Guard aims to fulfill institutional needs to ensure security and safety within national waters. This study aims to analyze the essential role of BAKAMLA in maritime law enforcement and identify the regulatory challenges it faces. Using a normative juridical approach, this research examines various legal frameworks related to maritime institutions and authority. The findings reveal that overlapping regulations and authority among institutions such as the Indonesian Navy (TNI AL), the National Police (POLRI), the Ministry of Marine Affairs and Fisheries (KKP), and others significantly hinder BAKAMLA’s effectiveness. Therefore, harmonization of maritime legal systems and regulations is urgently needed. It is recommended to enact a Coast Guard Law as a single regulation that designates BAKAMLA as the main coordinator of maritime law enforcement. This reform is expected to improve inter-agency coordination, integrate early detection systems, and strengthen Indonesia’s maritime sovereignty and security.